2008
DOI: 10.1007/s00464-008-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Is right laparoscopic donor nephrectomy right?

Abstract: Right laparoscopic donor nephrectomy requires less operating time than, and is associated with similar outcomes for donors and recipients as, left laparoscopic donor nephrectomy. Right laparoscopic donor nephrectomy may be preferable in general and should be considered when multiple renal vessels are present on the left side and/or when preoperative function of the left kidney is greater than the right.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Compared to the large published series of (hand-assisted) laparoscopic nephrectomies, the RPDN operation time was clearly shorter [4,19,20], demonstrating that RPDN is relatively easy to perform. The clear view onto renal vessels provides a safe procedure for left-and right-sided kidney donation.…”
Section: Discussionmentioning
confidence: 81%
“…Compared to the large published series of (hand-assisted) laparoscopic nephrectomies, the RPDN operation time was clearly shorter [4,19,20], demonstrating that RPDN is relatively easy to perform. The clear view onto renal vessels provides a safe procedure for left-and right-sided kidney donation.…”
Section: Discussionmentioning
confidence: 81%
“…described worse outcome for right kidneys, with significantly more renal vein thrombosis. One RCT, one prospective and five retrospective studies concluded that right sided‐donor nephrectomy is also justified, and some studies even indicate the superiority of the right side [72–78] (level 1b evidence) (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Keller et al reported that 36 right-sided procedures out of 230 LDNs showed similar results in EBL, amount of blood transfusion, operative time, LOS, and delayed graft function compared with left-sided HALDN [20]. There have been more reports about the excellent surgical outcomes of right laparoscopic donor nephrectomy compared with left-sided operations [21-23]. …”
Section: Discussionmentioning
confidence: 99%